2019
DOI: 10.3390/ijerph16060982
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of HLA-G in Women with High-Risk Pregnancy and Their Partners with Regard to Possible Complications

Abstract: The understanding of the molecular and biochemical characteristics of the human leukocyte antigen-G (HLA-G) is important because of the diverse influence of this antigen’s polymorphisms on the course of a pregnancy. The aim of our study was to assess how the variation of the HLA-G allele and the HLA-G 14-bp ins/del polymorphism influence predisposition to a complicated pregnancy. The clinical material consisted of parental pairs with complicated pregnancies (210 women; 190 men). The control group included pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, a recently published meta-analysis (37) on the impact of 14-bp ins/del polymorphism in recurrent miscarriage after natural or artificial conception revealed that women of European countries with the HLA-G 14-bp insertion/insertion homozygous genotype have a significantly higher prevalence of recurrent miscarriage. A study among another Polish group (53) indicated that the frequencies of the 14-bp ins/del genotypes in the 3 ′ -UTR of the HLA-G gene in groups with reproductive disorders did not report significant differences with the control group, and this result is concordant with our study. However, they suggest that the risk of complications in pregnancy is influenced rather by the particular alleles like HLA-G 10101, HLA-G 10108, and HLA-G 10106, not SNPs.…”
Section: Discussionsupporting
confidence: 92%
“…However, a recently published meta-analysis (37) on the impact of 14-bp ins/del polymorphism in recurrent miscarriage after natural or artificial conception revealed that women of European countries with the HLA-G 14-bp insertion/insertion homozygous genotype have a significantly higher prevalence of recurrent miscarriage. A study among another Polish group (53) indicated that the frequencies of the 14-bp ins/del genotypes in the 3 ′ -UTR of the HLA-G gene in groups with reproductive disorders did not report significant differences with the control group, and this result is concordant with our study. However, they suggest that the risk of complications in pregnancy is influenced rather by the particular alleles like HLA-G 10101, HLA-G 10108, and HLA-G 10106, not SNPs.…”
Section: Discussionsupporting
confidence: 92%
“…Further studies related pregnancy success to other HLA‐G polymorphisms: some groups concluded that the risk of complications in pregnancy is influenced by the HLA‐G 10101, HLA‐G 10108, and HLA‐G 10106 alleles and is not influenced by the 14‐bp ins/del polymorphism in the 3'UTR of the HLA‐G gene (Sipak et al., 2019) or that the association of HLA‐G with recurrent miscarriage was not related to single polymorphisms in the 3'‐UTR, but rather depended on haplotypes, such as the UTR‐4 haplotype, which included +3003C, and was found significantly lower in women with recurrent miscarriage (Meuleman et al., 2018).…”
Section: Hla‐g and Pregnancymentioning
confidence: 99%
“…Koc et al (26) found that the deletion of 14-bp was more common in the examined abortion group, but the difference was not significant. By contrast, Hashemi et al (21) and Sipak et al (27) showed that the HLA-G 14-bp Ins/Del polymorphism may confer RSA risk. Although other studies have evaluated the role of 14-bp Ins/Del polymorphisms in RSA, the results remain controversial (6,13,(22)(23).…”
Section: Discussionmentioning
confidence: 93%